Molecular epidemiology, genetic diversity, antibiotic resistance and pathogenicity of Stenotrophomonas maltophilia complex from bacteremia patients in a tertiary hospital in China for nine years - Wang, Lifeng; Wang, Yu; Ye, Kun; Qiu, Xuemei; Zhao, Qiang; Ye, LiYan; Yang, Jiyong (Frontiers in Microbiology, 2024)
The Stenotrophomonas maltophilia complex (Smc) has emerged as a significant nosocomial pathogen contributing to increased mortality rates, particularly in case of bloodstream infections.This study employed whole-genome sequencing (WGS) to assess the genetic diversity, antimicrobial resistance profiles, molecular epidemiology and frequencies of virulence genes among 55 S. maltophilia isolates obtained from bacteremic cases over a 9-year period.Results: Based on the threshold of 95% average nucleotide identity (ANI) and 70% digital DNA-DNA hybridization (dDDH) for genospecies delineation, we classified 37 isolates into 6 known species, all belonging to the Smc. The remaining 18 isolates sequenced in this study were assigned to 6 new genomospecies. Among the 55 isolates, we identified 44 different sequence types (STs), comprising 22 known and 22 novel allele combinations. The resistance rate of Smc against trimethoprim-sulfamethoxazole (TMP/SMX) was found to be 3.6%, with the sul1 and class one integron integrase genes (intI) detected in these isolates. All Smc isolates were susceptible to minocycline. Furthermore, all Smc strains harbored the motA, pilU, smf-1 and Stmpr2 genes.Genomospecies 1 (100%, n=9), Stenotrophomonas maltophilia (84.21%, n=19) and Stenotrophomonas sepilia (71.43%, n=7) demonstrated a higher percentage of the afaD gene, which was also associated with a higher separation rate. In addition to motA, pilU, smf-1 and Stmpr2 genes, all S. maltophilia strains (100%) contained entA, gspD, KatA and stmPr1 genes, while all genomospecies 1 strains (100%) contained afaD, entA, gspD and KatA genes.Our study highlights the genetic diversity among Smc isolates from patients with bacteremia, revealing 22 novel ST types, 58 new alleles and 6 new genomospecies. S. maltophilia and S. pavanii were found to carry more virulence factors, emphasizing the importance of accurate strain identification. Minocycline emerged as a promising alternative antibiotic for patients who were resistant to TMP/SMX.